Pengaruh Kredibilitas Dan Kepribadian Dosen Dalam Mengajar Terhadap Motivasi Belajar Mahasiswa Jurusan Komunikasi Penyiaran Islam Fakultas Dakwah Institut Agama Islam Negeri Syekh Nurjati Cirebon - F. Nurfalah; L. Maya; Widiyanti . (Jurnal Komunikasi Pembangunan, 2011)
Abstract This implies that the learning process is a lecturer and student interaction process based on a didactic relationship in order to achieve educational goals. The purpose of this study namely: (1) To determine the influence of the credibility‘s lecturers to student learning motivation, (2) To determine the influence of personality lecturers to student learning motivation, (3) To determine the effect of credibility and personality of  lecturers to student learning motivation. The research method used  was descriptive survey method, with a relatively large population in a way determine a representative sample of the population, by spreading questionare. With quantitative analysis techniques, namely the study variables analyzed with statistical formulas were supported by data. The research result were (1) There is a positive and significant effect between the credibility of lecturers in teaching to student learning motivation 22,6% with a large influence of X1 (credibility) 0,424; (2) There is a positive and significant effect between personality lecturers in teaching to student learning motivation at 14,6% with a large influence of X2 (Personality) 0,316; (3) There are positive and significant between the effects of credibility and personality to the teaching faculty in student learning motivation was 37,2% or 0,372 Keywords: credibility, personality, motivation